Implementation of Tahfidzul Qur'an: Analysis of Implementation, Challenges, and Impacts on Student Learning and Development - Yusuf Yusuf; Darodjat Darodjat; Zakiyah Zakiyah; Ibnu Hasan (Green Publisher Indonesia, 2025)
Tahfiz Al-Qur'an education at the Madrasah Ibtidaiyah level represents a strategic initiative in preparing a generation that is not only academically competent but also possesses noble character (akhlāq al-karīmah) and strong faith (īmān). This study explores the implementation of the Tahfiz Al-Qur'an program at Madrasah Ibtidaiyah Muhammadiyah Dumeling, Wanasari, Brebes, focusing on its execution, challenges, and impact on students' learning and holistic development. Employing a qualitative descriptive method, data were collected through interviews, observations, and documentation analysis. The findings reveal that the Tahfiz program is integrated into the daily curriculum, featuring scheduled memorization (halaqah) sessions guided by trained instructors (mu'allim/mu'allimah). Despite facing obstacles such as limited instructional time, varying student memorization aptitudes (isti'dād al-hifz), and insufficient parental engagement, the program contributes positively to students' discipline (tarbiyat al-inzibāṭiyyah), spiritual development (al-tanmiyah al-rūḥiyyah), and cognitive growth. Furthermore, it enhances students' intrinsic motivation (al-dāfiʿiyyah al-dākhiliyyah) and concentration (al-tarkīz) in general academic subjects. The study underscores the critical need for sustained institutional support, proactive parental involvement (musāhamat al-wālidayn), and innovative pedagogical strategies to optimize the program's effectiveness and educational outcomes.